Historical Legacy and Policy Effectiveness: the Long-Term Influence of pre-Unification Borders in Italy - Guido de Blasio; Giovanna D'Adda (European Regional Science Association (ERSA), 2014)
This paper investigates the interplay between cultural traditions and policy effectiveness. It explores the differential impact of a large development program (Cassa per il Mezzogiorno), implemented for four decades, starting in the 1950s, to stimulate convergence between Italy's South and the more developed North, on municipalities with different histories. Namely, we consider a sample of municipalities located on either side of the historical border of the Kingdom of Sicily, whose legacy is considered, from Putnam (1993) onwards, to be a prime-facie cause of Southern Italy's underdevelopment. Having been part of the Kingdom of Sicily is associated with a negative impact of development policies, but only when the allocation of development funds through the Cassa per il Mezzogiorno suffered from low quality of governance and was driven by political considerations rather than by efficiency ones.
Keywords: N4; O2; 330; Economic development; History; Social capital; Italy